The Versatile Link common project: feasibility report - Vasey, F; Hall, D; Huffman, T; Kwan, S; Prosser, A; Soos, C; Troska, J; Weidberg, T; Xiang, A; Ye, J (2012)
The Versatile Link is a bi-directional digital optical data link operating at rates up to 4.8 Gbit/s and featuring radiation-resistant low-power and low-mass front-end components. The system is being developed in multimode or singlemode versions operating at 850 nm or 1310 nm wavelength respectively. It has serial data interfaces and is protocol-agnostic, but is targeted to operate in tandem with the GigaBit Transceiver (GBT) serializer/deserializer chip being designed at CERN. This paper gives an overview of the project status three and a half years after its launch. It describes the challenges encountered and highlights the solutions proposed at the system as well as the component level. It concludes with a positive feasibility assesment and an outlook for future project development directions. © 2012 IOP Publishing Ltd and SISSA.